Broad-based Employee Ownership in Great Reset of capitalism - A. V. Lozhnikova; O. V. Kudelina (Модернизация, инновация, развитие, 2022)
Purpose: the authors explore the Role of Employee Ownership in the context of the Great Reset of Capitalism.Methods: in contrast to the theory of stakeholder capitalism, this article discusses an alternative point of view on the reset of capitalism – through the Broad-based Employee Ownership of companies in the world and Russian economy. The article criticizes G. Dow's methodological approaches and the underestimation on the contribution of Labour-managed firms to the world economy. The criterion of "45 founders or more" is applied to the mass ownership of employees, with a minimum number of founders of a cooperative of 5 persons.Results: the article presets results of two empirical studies. The first is to verify the current assessment of the head of the National Center for Worker Ownership (NCEO) on the significant role of Employee Ownership. Since neither the Employee Stock Ownership Plan (ESOP) nor its analogues are implemented in Russia, the second empirical study was conducted on an array of 15,086 agricultural cooperatives representing small and medium-sized businesses in the Russian Federation.Сonclusions and Relevance: it is concluded that the NCEO assessment was fully confirmed, and accordingly, G. Dow's assessment was refuted. The share of medium-sized enterprises-agricultural cooperatives with mass ownership of workers (45 founders or more) in the general database of enterprises-agricultural cooperatives is estimated to be an order of magnitude higher than the share of medium-sized enterprises in the total number of small and medium-sized enterprises (SMEs). To improve the mechanism of state financial support in the long term, new directions havebeen identified: the organizational and legal the form of a small and medium-sized business entity, the ownership and Broad-based employee ownership (founders /co-owners) of companies.